2016
DOI: 10.1111/aab.12293
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoctonia solaniinjuries in oilseed crops in Finland and impacts of different crop management practices on disease incidence and severity

Abstract: A disease survey in Finnish oilseed Brassica (OSR) fields in 2007-09 revealed the widespread occurrence and several fold increase of necrotic stem base lesions and severely injured blackened roots in comparison to a corresponding survey carried out in 1984-89. Rhizoctonia solani was the predominant fungi detected in the isolations and was followed by several species of Fusarium and Thielaviopsis basicola. In 60% of the samples all three species were detected together. Only the R. solani AG 2-1 strains isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…solani and T . basicola was found in the variants with reduced tillage and fertilization [ 50 ], which may be due to different geo-climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…solani and T . basicola was found in the variants with reduced tillage and fertilization [ 50 ], which may be due to different geo-climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The shares of all remaining crops increased, but especially rapeseed gained more parcels as did peas, winter rye and spring wheat (Table 2). The tool acknowledges the need for a lagperiod for cultivation, depending on the crop, to avoid increases in their crop protection risks (Hannukkala et al, 2016;Huusela-Veistola & Jauhiainen, 2006).…”
Section: Features Performance and Limitations Of The Tool Compared To The Goalsmentioning
confidence: 99%
“…Kesimci et al (2016) found that the sowing date significantly influenced the root-rot and wilt diseases of faba bean cultivars. Hannukkala et al (2016) found that late sowing date increased the risk for high incidence of stem base lesions in oil seed crops.…”
Section: Introductionmentioning
confidence: 99%